2013
DOI: 10.4049/jimmunol.1103779
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Hypoxia-Inducible Factor-1α Is Essential for Skeletal Muscle Regeneration in Mice

Abstract: The outstanding regeneration ability of skeletal muscle is based on stem cells that become activated and develop to myoblasts after myotrauma. Proliferation and growth of myoblasts result in self-renewal of skeletal muscle. In this article, we show that myotrauma causes a hypoxic microenvironment leading to accumulation of the transcription factor hypoxia-inducible factor-1 (HIF-1) in skeletal muscle cells, as well as invading myeloid cells. To evaluate the impact of HIF-1 in skeletal muscle injury and repair,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 36 publications
(65 reference statements)
8
52
1
2
Order By: Relevance
“…To assess a definitive role of HIF1 in myeloid cells, further analysis at later time points of regeneration (i.e., 3 wk) is required (31). Moreover, the study by Scheerer et al (30) reported no alteration of myeloid HIF-1a deletion on MP infiltration or on MP polarization, which is in agreement with the data presented in this article in two models of sterile inflammation. Scheerer et al's (30) study reported a transient delay in the number of F4/80 + cells, suggesting a defect in the proliferation of some MPs in the HIF1aKO strain.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…To assess a definitive role of HIF1 in myeloid cells, further analysis at later time points of regeneration (i.e., 3 wk) is required (31). Moreover, the study by Scheerer et al (30) reported no alteration of myeloid HIF-1a deletion on MP infiltration or on MP polarization, which is in agreement with the data presented in this article in two models of sterile inflammation. Scheerer et al's (30) study reported a transient delay in the number of F4/80 + cells, suggesting a defect in the proliferation of some MPs in the HIF1aKO strain.…”
Section: Discussionsupporting
confidence: 81%
“…Besides its role in hypoxia and in inflammation under normoxic conditions, HIF-1 is involved in skeletal muscle homeostasis and physiology (43,(49)(50)(51)(52). Recently, it has been claimed that myeloid HIF-1a was essential for skeletal muscle regeneration after a soft trauma (30). Our results, showing no alteration of skeletal muscle regeneration in mice depleted for myeloid HIFs in two different models of sterile injury dispute this assertion.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations